Psychological Distress and Non-Suicidal Self-Injury: The Mediating Roles of Rumination, Cognitive Reappraisal and Expressive Suppression - Richmond, S.; Hasking, Penelope; Meaney, R. (2015)
This study sought to explore the relationships between depression, anxiety, stress, and non-suicidal self-injury (NSSI), and the mediating roles of rumination and emotion regulation in this relationship. The sample comprised 1,586 Australian university students who completed a self-report questionnaire assessing the relevant variables. Of the sample, 8.9% engaged in NSSI in the 4 weeks prior to the survey. Depression, anxiety, and stress each exerted a direct effect on NSSI, and each relationship was mediated by cognitive reappraisal. The relationship between stress and NSSI was also mediated by expressive suppression. The results imply intervention efforts aimed at teaching adaptive emotion regulation strategies for students experiencing high levels of psychological distress may reduce the frequency of NSSI.